Estudo de um sistema embarcado para sinalização de ultrapassagem e análise de risco de colisão frontal - Moreira, Luciano Gonçalves (2017)
Traffic accidents are one of the biggest causes of death in the world. In Brazil in 2016 there was a 6.8% reduction in the number of deaths compared to 2015, but in the Carnival holiday of 2017 there was an increase of 24% in relation to 2016. Overtakes in a prohibited place or due to failure of the driver's evaluation are the biggest culprits due to frontal collisions on single lane highways. Several technologies have been developed to reduce road deaths, such as advanced driver assistance systems (ADAS) and dedicated short-range communications (DSRC), gradually implemented in new vehicles, especially those of a high -end, both with low application in prevention of frontal collisions in overtaking. Thus, this work proposes the study of a system for signaling overtaking and analysis of the risk of frontal collision, based on concepts of kinematics related to meeting and overtaking of mobile. For study and evaluation, two electronic devices were built with the embedded system, plus GPS receiver and radio frequency communication, used to exchange information between the vehicles involved in the maneuver. A simulation with the Geogebra software was also developed to verify that the embedded system performs the calculations and analyzes correctly if there is a risk of frontal collision during overtaking. The tests were carried out in the field simulating overtaking in a controlled environment, with two vehicles using the electronic devices traversing stretches on single lane highways, the purpose of which was to co llect data on the transmissions, overtaking calculations and against vehicle in the opposite direction. The analysis of the data shows that the system has signaled the intention to overtake vehicles and has performed these calculations accurately by correctly analyzing the risk of a possible frontal collision occurring during the maneuver and can thus assist drivers in judging whether they overtake or not. However, the performance of the hardware demonstrates the need for improvements not to compromise this goal, as it presented 492 m maximum signal reach, average latency of 112 ms and a total of 21% packet loss. Despite the hardware limitation, due to the use of low cost devices, the system can be useful in preventing frontal collisions during overdrive.